14 Oct '07 19:09

I'm new to the wonderful world of algebra and I have a question

equation 5x + 3y = 27 I have never solved equations like this and have not been taught how, but I can prove that 27=27,but i cant solve for the variables;at least not using algebra

here is what I do

solve for x in terms of y so, x=(27-3y)/5 and plug that into the original equation

5((27-3y)/5) + 3y = 27

27-3y +3y = 27

27=27...................why is this happening?

We are studying symmetries in class and and I want to prove that one equation equals or does not equal another,....other than the substitution of numbers into them.

for instance: does 5x-5y=0=-5x+5y,...the check to see if they are symmetric to the origin........in this case they would because x=y making the equation symmetric to the origin

I found this out by saying the addition of the two equations should equal zero 5x-5y+(-5x + 5y) = 0

My question is, by using this method where will I run into complications if any?

equation 5x + 3y = 27 I have never solved equations like this and have not been taught how, but I can prove that 27=27,but i cant solve for the variables;at least not using algebra

here is what I do

solve for x in terms of y so, x=(27-3y)/5 and plug that into the original equation

5((27-3y)/5) + 3y = 27

27-3y +3y = 27

27=27...................why is this happening?

We are studying symmetries in class and and I want to prove that one equation equals or does not equal another,....other than the substitution of numbers into them.

for instance: does 5x-5y=0=-5x+5y,...the check to see if they are symmetric to the origin........in this case they would because x=y making the equation symmetric to the origin

I found this out by saying the addition of the two equations should equal zero 5x-5y+(-5x + 5y) = 0

My question is, by using this method where will I run into complications if any?